Implementation of muslim friendly hospitality services requirements 2015 and shariah-based quality management system guidelines 2015 in shariah-compliant hotels in Malaysia - Abd Razak, Nur Athirah (2019)
As a top preferred destination for Muslim travelers worldwide, Malaysia received 5,152,947 Muslim travelers from all around the world in 2015 as reported by Islamic Tourism Centre. There are several attributes of Shariah-compliant hotel developed by Henderson and Stephenson. However, their attributes of Shariah- compliant hotels are based on their own experience and knowledge about Shariah-compliant hotels. Most previous studies focused only on a certain aspect such as the hotel room design, accessories, and halal food. Therefore, the objectives of this study are: 1) To explore whether the hospitality services provided by Shariah-compliant hotels are Muslim friendly by the Malaysian standard from the perspective of organization strategy, employees, communication, facilities, and services; 2) To explore whether the strategy in the management of Shariah-compliant hotels in Malaysia is parallel with the Malaysian standard with regards to management responsibility, resource management, and improvement; 3) To identify the challenges faced by Shariah- compliant hotels in Malaysia in implementing Muslim friendly hospitality services. In order to achieve the objectives of this study, the qualitative approach was used. Collection of data was conducted via in-depth semi-structured interviews with employees from different departments and observations of three hotels: 1) De Palma Hotel, 2) Adya Hotel, 3) Grand Bluewave Hotel. Regarding Muslim friendly services, the three hotels implement Muslim friendly services especially in providing halal food and hotel room facilities, whereas on Shariah-based quality management system, the three hotels operate according to the Shariah- based quality management system, although only minimal. Based on the findings, this study recommends hotel operators to acquire intensive knowledge regarding Shariah-compliant hotels in terms of their operations and to obtain information on the extent of Shariah compliance and Muslim friendly environment as practiced in Malaysian hotels.